COMPANY HEALTH LEVEL ANALYSIS WITH FINANCIAL ASPECTS AT PT PERUSAHAAN GAS NEGARA TBK - Baniady Gennody Pronosokodewo; Tantri Dyah Ayu Lestari; Sri Suryaningsum (CV. Fahr Publishing, 2023)
The company's financial health information is needed to protect the company's existence from competitors. Companies that need to be assessed for their financial health are State-Owned Enterprises, therefore the Minister of State-Owned Enterprises Decree No: Kep-100/MBU/2002 appears to assess the soundness of SOEs. This study aims to determine the level of financial health of the company at PT Perusahaan Gas Negara (Persero) Tbk for the period 2018-2021. By using eight (8) indicators, namely: Return On Equity (ROE), Return On Investment (ROI), Current Ratio, Cash Ratio, Collection Periods (CP), Inventory Turnover (PP), Total Asset Turn Over (TATO) , Ratio of total own capital to total assets. The results of the discussion can be seen that the financial performance of PT Perusahaan Gas Negara (Persero) Tbk in the last four years is in an unhealthy condition, it is hoped that the company will be able to improve the level of financial health.